The Association Between Hospital Finances and Complications After Complex Abdominal Surgery. Issue 2 (August 2015) - Knechtle, William S.; Perez, Sebastian D.; Medbery, Rachel L.; Gartland, Bryce D.; Sullivan, Patrick S.; Knechtle, Stuart J.; Kooby, David A.; Maithel, Shishir K.; Sarmiento, Juan M.; Shaffer, Virginia O.; Srinivasan, Jahnavi K.; Staley, Charles A.; et al.
<x xml:space="preserve">Abstract</x> Objective: To determine the relationship between complications after 3 common general surgery procedures and per-episode hospital finances. Background: With impending changes in health care reimbursement, maximizing the value of care delivered is paramount. Data on the relative clinical and financial impact of postoperative complications are necessary for directing surgical quality improvement efforts. Methods: We reviewed the medical records of patients enrolled in the American College of Surgeons' National Surgical Quality Improvement Program who underwent pancreaticoduodenectomy, hepatectomy, and colectomy at a single academic institution between September 2009 and August 2012. Clinical outcomes data were subsequently linked with hospital billing data to determine hospital finances associated with each episode. We describe the association between postoperative complications, hospital length of stay, and different financial metrics. Multivariable linear regression modeling tested linear association between postoperative outcomes and cost data. Results: There was a positive association between the number of surgical complications, payments, length of stay, total charges, total costs, and contribution margin for the three procedures. Multivariable models indicated that complications were independently associated with total cost among the selected procedures. Payments increased with complications, offsetting increased costs. Conclusions: In the current fee-for-service environment, the financial incentives are misaligned with quality improvement efforts. As we move to a value-driven method of reimbursement, administrators and health care providers alike will need to focus on improving the quality of patient care while remaining conscious of the cost of care delivered. Reducing complications effectively improves value.